SELECTION CRITERION BASED ON TRAIT LINKAGES IN AFRICAN AND ASIAN PEARL MILLET [Pennisetum glaucum (L.) R. Br.] POPULATIONS TO ENHANCE PRODUCTIVITY - and T. RAMESH, K. SUDARSHAN PATIL, S. K. GUPTA, KULDEEP SINGH DANGI, D. SHASHIBHUSHAN, M. BALRAM (The Journal of Research, PJTSAU, 2019)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is commonly grown in the arid and semi-arid regions of Africa and Asia. It serves as staple food for the people living in relatively dry tracts of the India and Sub-Sahelian Africa and an important source of fodder/ feed for livestock and poultry. It can be cultivated evenin the poor infertile soils and drought prone environments, where no other cereal crop can survive. In India, currently pearl milletis cultivated on ~7.5 m ha area with grain production of 9.7 Mt with an average productivity of 1,305 kg ha-1(www.indiastat.com). The ultimate aim in most plant breeding programs is the improvement in the productivity of grains as measured in terms of the yield per unit area. The possibilities of achieving this goal through genetic improvement have been elucidated by evolving high yielding hybrids and varieties of pearl millet in Asiaand West Africa.